2010
DOI: 10.1021/la103927a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Force Mapping in the Study of Supported Lipid Bilayers

Abstract: Investigating the structural and mechanical properties of lipid bilayer membrane systems is vital in elucidating their biological function. One route to directly correlate the morphology of phase-segregated membranes with their indentation and rupture mechanics is the collection of atomic force microscopy (AFM) force maps. These force maps, while containing rich mechanical information, require lengthy processing time due to the large number of force curves needed to attain a high spatial resolution. A force cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Measurement of F B maps on multiple-phase lipid membranes therefore sets a link between local molecular interactions and the microscopic phase structure [21]. The increase in F B values of both the continuous and dispersed phases with decreasing temperature is consistent with other reports.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 3 more Smart Citations
“…Measurement of F B maps on multiple-phase lipid membranes therefore sets a link between local molecular interactions and the microscopic phase structure [21]. The increase in F B values of both the continuous and dispersed phases with decreasing temperature is consistent with other reports.…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Previous reports have shown that this approach successfully scales high features of ordered lipid domains as significantly more rigid than the l d phase at ambient temperature [17,21,40,56]. To the authors' knowledge, except for the DPPC/cholesterol study by Redondo-Morata et al [42] no previous AFM investigation of the temperature-dependence of the mechanical properties had been reported so far on multiple-component lipid bilayers.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
See 2 more Smart Citations
“…6 The study of how surfaces deform when probed with an AFM tip is a thoroughly researched field, and several well established theories exist which can relate the surface deformation to the load force and the Young's modulus of a substrate. [7][8][9][10] In the case of thin biological films, it has been shown that these theories can be adapted to determine elastic moduli if information about how the deformation of the film changes with load is known. [9][10][11] Assuming that the micelles at the surface behave elastically at measurable load forces, it might then be possible to apply adapted versions of these theories to micellar surfaces.…”
Section: Introductionmentioning
confidence: 99%